Understanding Student Engagement And Satisfaction With Chatgpt In Dental Education: A Qualitative Exploration - Jan, Hassan; Fatima, Atteeb; Ahmad, Mian Bilal; Arshad, Ayesha; Abideen, Malik Zain Ul; tareen, Jawad (Journal of Rawalpindi Medical College, 2024)
Objective: The study aimed to explore the engagement and satisfaction levels of dental students in Pakistan using ChatGPT as a supplementary learning tool. Method: Thematic analysis was conducted on qualitative data from semi-structured interviews with dental students. A purposive sampling strategy was employed to select participants, and data were collected through in-depth interviews until saturation. The data were analysed using the Bran and Clarke framework to identify key themes and sub-themes related to students' perceptions and experiences with ChatGPT. Results: The thematic analysis revealed several key themes and sub-themes related to students' engagement levels and satisfaction with ChatGPT. Themes included perceived utility, ease of access, interactive learning experience, relevance to learning needs, user interface experience, confidence in responses, personalisation of learning, challenges with ChatGPT (language barriers, technical issues, lack of human interaction, content limitations), and suggestions for improvement (language support, technical assistance, enhanced content generation, integration with classroom instruction). Conclusion: The findings highlighted the perceived utility and relevance of ChatGPT to students' learning needs. However, challenges such as language barriers, technical issues, and content limitations indicate areas for improvement. By addressing these challenges and incorporating suggestions for enhancement, ChatGPT has the potential to play a valuable role in dental education, complementing traditional teaching methods and preparing students for the future of dentistry.